A survey of the dialect geography of six towns of Pangasian Bautista, Pozorrubio, Dagupan City, Lingayen, Alaminos, Mangatarem - Fernandez, Revocata A. 1923- (s.n.], 1970)
The aim of the study is to conduct a survey of the dialect geography organized around the variable of lexical and phonological features in the six towns of Pangasinan namely: Bautista, Pozorrubio, Dagupan City, Lingayen, Alaminos, and Mangatarem. The study is primarily concerned with finding the degree of social and locational distribution of variations in dialect among specific age levels of speaker- middle-aged and adolescents, each including informants who are highly educated, better educated, and poorly educated or uneducated. Findings of the study reveal that the Pangasinan dialect has adopted many Ilocano words. However, there is a high mutual intelligibility and correspondence in the six towns in spite of the Ilocano influence.